Readiness for online distance learning (ODL) understanding the attitudes among students in UiTM Pahang / Azwan Shah Aminuddin ... [et al.] - Aminuddin, Azwan Shah; Mohd Azmi, Nor Farhana; Sulaiman, Mohd Azizul; Saini, Norhana Aini (2021)
This is a survey of 373 students enrolled in Diploma and Degree in Universiti Teknologi MARA, Pahang Campus. The main objective of this study is to determine the student’s readiness and attitudes towards online distance learning. Online distance learning is a new norm in many institutions of higher learning in Malaysia. Due to Coronavirus disease (COVID-19) pandemic, many universities are implementing online distance learning as their tools in teaching and learning as a new learning environment. This study used quantitative method with primary data through questionnaires distributed to 373 samples of students in UiTM Pahang. The Pearson correlation coefficient test is used to indicate the major variable contribute towards readiness among respondents. Meanwhile, multi regression test is used to found out the most attitude influence the readiness of online distance learning. It is found that attitude towards classroom interaction is the major variable among respondents in order to be ready for online distance learning. Respondents prefer to have interaction in the classroom first before they begin with online distance learning. Meanwhile, researchers also found that attitude towards online learning significantly contribute to the prediction of student’s readiness. Students attitude really give a major impact towards the readiness of online distance learning. This study also provides a descriptive picture for the universities on the attitude and expectation of students towards readiness of online distance learning